Challenges of Beginner Elementary School Principals in the Buffer Area of Surakarta Municipality - Nurjaningsih Nurjaningsih; Gunarhadi Gunarhadi; Sunardi Sunardi; Sukarmin Sukarmin (Green Publisher, 2024)
Elementary school (SD) principals play a crucial role in determining the success of education in schools. In the buffer areas of Surakarta Municipality, elementary school principals often face unique challenges that impact their performance. This study aims to identify the challenges faced by novice elementary school principals in the buffer areas of Surakarta Municipality. This study employs a descriptive method with data collection conducted through a survey technique. Respondents consist of 60 novice school principals who have served for less than three years. The collected data are analyzed through three stages: data reduction, data presentation, and conclusion drawing. The results show that novice elementary school principals in the buffer areas of Surakarta Municipality face various challenges, such as a lack of experience and knowledge, limited resources, and insufficient community support. To overcome these challenges, principals employ various strategies, such as attending training and seminars, building networks with other schools, and collaborating with the community. This study provides recommendations for enhancing support for novice principals to improve the quality of education in these areas.